Standardized Mortality Ratios in Capitation Funding Models: Emiprical Issues from Canadian Data - Kelly Bedard; John Dorland; Allan Gregory; Mark Rosenberg (Queen's University, Department of Economics, 1997)
Needs based capitation models have been suggested as an alternative to funding methods based on historical utilization patterns. The standardized mortality ratio (SMR) applied in conjuction with an age/gender adjustment is the most widely adopted measure of relative need. This paper addresses a number of important index construction issues using Canadian data. These include the influence exerted by the reference population (national versus provincial), the age structure (excluding people over 64 versus 74), the optimal period over which to average the SMR in order to smooth meaningless fluctuations, and the correspondence between SMRs, standard socio-economic indicators (i.e. unemployment, education, and income), health care 'need', and expenditures.
Keywords: I0; H51; 330; Standardized mortality ratios; Capitation funding; Region; Age; Gender